(untitled) (Revista Brasileira Multidisciplinar, 2025)
This essay brought to the light, the debate concerning the use of the widespread term indian, proposing to investigate the way in which this denomination affects the quality of the Multidisciplinary Indigenous Health Team workers. Defined as a qualitative exploratory and descriptive approach, our research took into consideration two theoretical-methodological axes: the hermeneutic-dialectic method as well as the Health Surveillance Model. Throughout the work, we showed that it is coherent to replace the generic name indian for a more affirmative reference of indigenous self-identification, in the exercise of an educative; supportive and critical citizenship, aligned with the dialogical and ethical process necessary in territories marked by intercultural coexistence. We conclude that it is not just about exchanging one word for another, but in how it highlights the expression of an improved cultural sensitivity, by guiding the ability to rethink some long-rooted conceptions. The permanent and coherent practice of the recommended healthcare model contributed to catalyze and encourage a sense of respect for cultural diversity, showing impact over the resolution actions, when in front of vulnerabilities and health needs of indigenous communities originating in Brazil.